ANALISIS PEMENUHAN KEWAJIBAN PERPAJAKAN PERUSAHAAN MEDIA ONLINE DI KOTA AMBON - Mediana Azra Syahputri Jempot; Monika Handojono; Junus Paulus Patty (P3M Politeknik Negeri Ambon, 2023)
This study aims to determine the fulfilment of tax obligations of an online media company, namely PT. Medira Media Sejahtera for tax period of 2021 based on Law Number 11 of 2020 concerning Job Creation. This study used descriptive quantitative method to analyze the data of income statement of PT. Medira Media Sejahtera of 2021. The findings of the study indicate that in the year of 2021, there are some tax obligations that have not yet been fulfilled by the company. They are income tax article 4 paragraph (2) and income tax Article 17. The major reason is the lack of understanding regarding tax obligations for corporate taxpayer. However, in addition to the article mentioned, the company has fulfilled the tax obligations that must be paid.